2015
DOI: 10.1007/s10734-015-9900-z
|View full text |Cite
|
Sign up to set email alerts
|

Following the leader? Network models of “world-class” universities on Twitter

Abstract: Much research on higher education has engaged with the concept of "world-class" universities and the complementary surge of interest in global university rankings. Literature takes a variety of positions on these intertwined phenomena, from vocal support of rankings and "world-class" aspirations to critical analyses of their influence and ideological underpinnings. Despite these differences, there is widespread consensus on the obsession with "world-class" status and the emergence of a new global field of comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 41 publications
0
24
0
1
Order By: Relevance
“…The academic literature on the use of social networking platforms such as Twitter™ for research purposes is in its infancy, thus is unsurprisingly limited. One recent paper, however, discusses how social media communications can reveal insight into a university's prestige (Shields, 2015). This is because social media enables connections, thus providing a means for public engagement, institutional branding and research outputs.…”
Section: Using Twitter™ For Healthcare Researchmentioning
confidence: 99%
See 3 more Smart Citations
“…The academic literature on the use of social networking platforms such as Twitter™ for research purposes is in its infancy, thus is unsurprisingly limited. One recent paper, however, discusses how social media communications can reveal insight into a university's prestige (Shields, 2015). This is because social media enables connections, thus providing a means for public engagement, institutional branding and research outputs.…”
Section: Using Twitter™ For Healthcare Researchmentioning
confidence: 99%
“…It was found that universities may even seek to preserve their elite status via Twitter™. The ranking of an institution increases the likelihood of followers and mentions, and the strongest predictor of a Twitter™ connection is an existing tie or mutual acquaintance (Shields, 2015).…”
Section: Using Twitter™ For Healthcare Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…This is most clearly manifested in the development of "new media" -computer technologies facilitating interactive communication on the Internet, corporate portals, blogs, applications for mobile devices, and social networks, which include Facebook, VKontakte, My World, and Twitter. Today universities actively "submerge" into this communicative environment because of a number of reasons, including the need to improve their position in the world university ranking and the need to apply new educational technologies meeting modern sociocultural tendencies [7,8,9].…”
Section: Methodsmentioning
confidence: 99%